Long segment and short segment familial Hirschsprung's disease: variable clinical expression at the RET locus. Issue 8 (August 1994) - Edery, P; Pelet, A; Mulligan, L M; Abel, L; Attié, T; Dow, E; Bonneau, D; David, A; Flintoff, W; Jan, D
Abstract : Hirschsprung's disease (aganglionic megacolon, HSCR) is a frequent condition of unknown origin (1/5000 live births) resulting in intestinal obstruction in neonates and severe constipation in infants and adults. In the majority of cases (80%), the aganglionic tract involves the rectum and the sigmoid colon only (short segment HSCR), while in 20% of cases it extends toward the proximal end of the colon (long segment HSCR). In a previous study, we mapped a gene for long segment familial HSCR to the proximal long arm of chromosome 10 (10q11.2). Further linkage analyses in familial HSCR have suggested tight linkage of the disease gene to the RET protoncogene mapped to chromosome 10q11.2. Recently, nonsense and missense mutations of RET have been identified in HSCR patients. However, the question of whether mutations of the RET gene account for both long segment and short segment familial HSCR remained unanswered. We have performed genetic linkage analyses in 11 long segment HSCR families and eight short segment HSCR families using microsatellite DNA markers of chromosome 10q. In both anatomical forms, tight pairwise linkage with no recombinant events was observed between the RET proto-oncogene locus and the disease locus (Zmax = 2.16 and Zmax = 5.38 for short segment and long segment HSCR respectively at 0 = 0%) Multipoint linkage analyses performed in the two groups showed that the maximum likelihood estimate was at the RET locus. Moreover, we show that point mutations of the RET proto-oncogene occur either in long segment or in short segment HSCR families and we provide evidence for incomplete penetrance of the disease causing mutation. These data suggest that the two anatomical forms of familial HSCR, which have been separated on the basis of clinical and genetic criteria, may be regarded as the variable clinical expression of mutations at the RET locus.